Vertical diffusion of pollutants in the atmospheric boundary layer - Ulke, Ana G. (1993)
An atmospheric diffusion model is used to study the main features of vertical distribution of pollutants released from a continuous point source at different heights in a thermally stratified atmospheric boundary layer. The model is based on the two-dimensional advection-diffusion-deposition equation, with vertical profiles of wind and eddy diffusivity for the atmospheric boundary layer. The formulation permits studying the influence of surface roughness, atmospheric stability, mixing depth and source height on concentration distributions. Numerical simulations of atmospheric diffusion experiments are done. From the two-dimensional concentration fields, different para-meters are calculated in terms of the second, third and fourth order statistical moments which characterize vertical distributions of material. The computed values are satisfactorily compared with those evaluated from observational data. The vertical dispersion coefficient (second order moment root mean square) is also compared with those proposed by other authors.